Influence of Infill Geometry and Density on the Mechanical Properties of 3D-Printed Polylactic Acid Structure - Jozef Jaroslav Fekiač; Lucia Kakošová; Michal Krbata; Marcel Kohutiar; Maroš Eckert; Zbynek Studeny; Andrej Dubec (Journal of Manufacturing and Materials Processing)
Additive manufacturing of polymer composites, also known as 3D printing, is one of the progressive technologies in material engineering. It enables the production of parts with complex geometries while optimizing material efficiency. Polylactide (PLA) is a widely used material in additive manufacturing due to its biodegradability and suitable mechanical properties. However, its brittleness and limited thermal stability require further modifications, such as modifying the filler structure or adding reinforcing materials. This paper focuses on analyzing the influence of different filler geometries and densities on the mechanical properties of PLA parts manufactured by the fused filament deposition (FFF) method. Three basic filler structures—cubic, gyroid and rectilinear—were investigated at different density levels from 20%, 40%, 60% and 80%. Experimental tests were performed according to ASTM D638 to determine the strength characteristics of the material. In addition to mechanical tests, dynamic mechanical analysis (DMA) and thermogravimetric analysis (TG) were performed to better understand the influence of the filling geometry on the thermal stability and viscoelastic behavior of the material. Experimental tests according to ASTM D638 showed that higher filling density improves mechanical properties. At 80% filling, the tensile strength reached 21.06 MPa (cubic), 20.53 MPa (gyroid) and 20.84 MPa (linear). The elastic modulus was highest with cubic filling (1414.19 MPa). The yield strength reached 15.59 MPa (cubic), 15.52 MPa (gyroid) and 14.30 MPa (linear).